Relational frame theory 20 years on: The Odysseus voyage and beyond. Issue 2 (11th January 2022) - Barnes‐Holmes, Dermot; Harte, Colin
Abstract : The seminal text on relational frame theory (RFT) was published 20 years ago and purported to offer a single overarching behavior‐analytic account of human language and cognition. In the years thereafter, an increasing number of empirical and conceptual articles, book chapters in edited volumes, and whole volumes devoted to the account emerged. In recent years, RFT has experienced a period of intense empirical and conceptual development, facilitated in part by a research grant awarded by the Flanders Science Foundation, under its Odysseus program. This research program aimed to advance and extend the RFT account beyond the rendition presented in the seminal Hayes et al. (2001) volume. The current article aims to provide an overview of this research program, the empirical work and concepts it gave rise to, and their implications for an RFT account of human symbolic language and cognition. Overall, therefore, the article provides an account of relatively recent developments in RFT that extend beyond the 2001 volume and thus will, we hope, inform future research and critiques of the theory going forward.